2020
DOI: 10.14412/1996-7012-2020-4-111-124
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive concentrate from small sea fish: evaluation of the efficacy and safety of the drug on the basis of the analysis of 37 clinical trials

Abstract: Injectable Alflutop® (the bioactive concentrate from small sea fish (BCSSF)) belongs to the pharmacological group of symptomatic slow-acting drugs for osteoarthritis. This drug has been widely used in our country for 25 years. During this time, 37 of its clinical trials (n=3676) have been conducted in Russia and post-Soviet countries, mainly in patients with knee osteoarthritis (OA) and nonspecific back pain. These are mainly open-label trials, a major portion of which has been performed at the good methodolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 37 publications
0
1
0
1
Order By: Relevance
“…In clinical trials, SSFE demonstrated chondroprotective (slowing the progression of osteoarthritis and the growth of osteophytes, reducing the degradation of the articular cartilage matrix), anti-inflammatory, antioxidant, and analgesic effects, and showed significant correction of joint and spinal function and improvement in quality of life [83][84][85][86].…”
Section: Chondroitin Sulphates In the Pathogenetic Therapy Of Systemi...mentioning
confidence: 99%
“…In clinical trials, SSFE demonstrated chondroprotective (slowing the progression of osteoarthritis and the growth of osteophytes, reducing the degradation of the articular cartilage matrix), anti-inflammatory, antioxidant, and analgesic effects, and showed significant correction of joint and spinal function and improvement in quality of life [83][84][85][86].…”
Section: Chondroitin Sulphates In the Pathogenetic Therapy Of Systemi...mentioning
confidence: 99%
“…В экспериментальных исследованиях было показано, что структурно-модифицирующий эффект биоактивного концентрата мелких морских рыб при ОА может быть свя-зан с ингибированием экспрессии протеаз, ответственных за каскад деградации ядерного белка аггрекана (экспрессия мРНК ADAMTS4); увеличением синтеза аггрекана и гиалуронана (активация экспрессии мРНК гиалуронан-синтазы, HAS1), а также с активацией основного регулятора транскрипции SOX9, ответственного за предотвращение деградации внеклеточного матрикса. Кроме того, этот препарат способен сдерживать прогрессирование болезни за счет стимуляции пролиферации хондроцитов, активации синтеза внеклеточного матрикса посредством модуляции трансформирующего фактора роста β (ТФРβ), ингибирования гиалуронидазы и окислительного стресса [26,27].…”
unclassified